Advances in management and utilization of invasive water hyacinth (Eichhornia crassipes) in aquatic ecosystems – a review. (17th February 2017) - Yan, Shao-Hua; Song, Wei; Guo, Jun-Yao
Abstract: The objective of this review is to provide a concise summary of literature in the Chinese language since late 1970s and focuses on recent development in global scenarios. This work will replenish the FAO summary of water hyacinth utilization from 1917 to 1979 and review ecological and socioeconomic impacts of the water hyacinth from 1980 to 2010. This review also discusses the debate on whether the growth of the water hyacinth is a problem, a challenge or an opportunity. Literature suggested that integrated technologies and good management may be an effective solution and the perception of water hyacinth could change from that of a notorious aquatic weed to a valuable resource, including its utilization as a biological agent for the application in bioremediation for removing excess nutrients from eutrophic water bodies at low cost. Key aspects on system integration and innovation may focus on low-cost and efficient equipment and the creation of value-added goods from water hyacinth biomass. In the socioeconomic and ecological domain of global development, all the successful and sustainable management inputs for the water hyacinth must generate some sort of social and economic benefit simultaneously, as well as benefiting the ecosystem. Potential challenges exist in linkages between the management of water hyacinth on the large scale to the sustainable development of agriculture based on recycling nutrients, bio-energy production or silage and feed production. Further research and development may focus on more detailed biology of water hyacinth related with its utilization, cost–benefit analysis of middle to large-scale application of the technologies and innovation of the equipment used for harvesting and dehydrating the plant.